Scope of the micropolitical school in an educational institution in the city of Lambaré, Paraguay - Gómez Giménez, Dina Noemí (2018)
There is a micro-political environment in school life. The general objective of this study was to analyze the micro-political scope of an educational institution in the city of Lambaré, Paraguay. The focus of the research was qualitative, design, case study and phenomenological, had a descriptive scope. The population was an institution of the same city, and the sample there were the representatives of the different classes of the Team of School Management and two more teachers. The skills have been used: observation, analysis of papers and interviews semi structured. It then proceeded to the organization of the data and the corresponding analysis; which has led to the conclusion that an educational institution has a special treatment, it is not like any organization, there are different groups well differentiated and specified with interests of different types, that each group according to its possibilities you want to keep some kind of control and power, using a variety of strategies.